Stress Corrosion Cracking. - Jones, Russell H. (ASM International, 2017)
This new second edition serves as a go-to reference on the complex subject of stress corrosion cracking (SCC), offering information to help metallurgists, materials scientists, and designers determine whether SCC will be an issue for their design or application; and for the failure analyst to help determine if SCC played a role in a failure under investigation.